Paleoproterozoic Saltakh Pluton, Anabar Shield: mineralogical composition, age and a geodynamic setting - Nikolai I. Gusev; Lyudmila Yu. Romanova (Записки Горного института)
The Saltakh Massif is located in the northern Anabar Shield, in the Saltakh shear-zone. It consists of two-pyroxene schists and plagiogneisses metamorphosed under granulite-facies conditions. Their chemical composition is consistent with that of a differentiated series of rocks ranging from gabbro to tonalites with abundant alaskitic gneissose granite veins and bodies. The rocks are mainly high-potassium (K2O/Na2O > 0.50), high-magnesium (mg# 50-70), low-titanium (TiO2 0.35-1.31 wt.%) with low TiO2 concentration in clino- and orthopyroxene. Normative olivine makes up 6-9 % of metagabbroic rocks. The rocks display well-defined negative Ti, Nb, Ta, and P anomalies typical of subduction magmatism. The two-pyroxene gneisses show high Sr/Y ratios of 67.6-88 and (La/Yb)N of 24.8-25.6. Saltakh rocks are part of a shoshonite series, as indicated by Nb/La, La/Yb, Th/Nb and Ce/Yb ratios. All the rocks display positive εNd(T) values of 1.9-4.1 and εSr(T) of 0.77-17.8 indicative of a mantle source of magma and T(Nd)DM of 2,20-2,26 Ga. U-Pb zircon dating (SHRIMP II) has shown that the protoliths of Saltakh melanocratic rocks were dated at 2100-2086 Ma, and those of two-pyroxene plagiogneisses of tonalite composition were dated at 2025±7 Ma. Alaskitic gneissose granites were dated at 1969±7 Ma. The study of the trace element composition of zircon has revealed general enrichment in LREE. High LREE concentrations are due to secondary zircon alterations and the shoshonitic pattern of the melt, the high-temperature conditions of crystallization, and an anomalous fluid regime. The geodynamic setting in which the Saltakh Massif was formed was consistent with a pericontinental magmatic arc. The formation of alaskitic gneissose granites was due to anatexis provoked by later collision processes. Saltakh magmatic rocks were formed simultaneously with magmatic rocks from the Khapchan prospect which occur farther south, and were studied earlier (2095±10 Ma tholeiitic metadiorites and 2030±17 Ma calc-alkaline metatonalites). We interpret them as part of a metamorphosed juvenile Paleoproterozoic suprasubduction complex.